Identification of Students' Misconceptions to the Kinetic Gas Theory in Physics - Nurulwati; A Halim; Mailizar; Muhammad Syukri; Mawarni Saputri (Postgraduate, University of Mataram, 2024)
This study aims to identify students' misconceptions on the material of Kinetic Gas Theory in physics learning. This study uses a qualitative approach and the type of research used is descriptive research. The subjects of this research were 20 students of class XI. The data was collected by means of a diagnostic test technique equipped with CRI (Certainty of Response Index) and free-guided interviews. The results of data analysis show that the average Lucky Guess level is 13%, concept understanding is 39%, not understanding concept is 20%, and average percentage of misconceptions are 28%. Based on the identification results, the highest misconceptions in students appear in the indicator of the question of calculating the ideal gas equation by 55%. The results of the analysis and interviews that have been carried out, misconceptions occur due to the students themselves because they do not understand the concept as a whole and the lack of interest of students to repeat the lesson.